A3.10 Plasma levels of heat shock protein 90 correlate with disease activity, lung involvement and skin fibrosis in systemic sclerosis. (13th February 2015) - Storkanova, H; Hulejova, H; Spiritovic, M; Prajzlerova, K; Skacelova, S; Becvar, R; Pavelka, K; Vencovsky, J; Distler, JH; Senolt, L; Tomcik, M
Abstract : Background: Our previous study demonstrated that Heat shock protein 90 (Hsp90) is overexpressed in the skin of patients with systemic sclerosis (SSc), in cultured SSc fibroblasts and preclinical models of SSc in a TGF-β dependent manner. We showed that Hsp90 is a new regulator of canonical TGF-β signalling and its inhibition prevents the stimulatory effects of TGF-β on collagen synthesis and dermal fibrosis in three preclinical models of SSc. 1 The aim of this study was to evaluate Hsp90 in the circulation of SSc patients and characterise its potential association with skin changes and SSc-related features. Methods: A total of 40 patients (36 females; mean age 53.9; disease duration 5.0 years; dcSSc/lcSSc = 9/31) who met the ACR classification criteria for SSc and 39 healthy individuals matched by age and sex were included. Plasma Hsp90 levels were measured by ELISA (eBioscience, Vienna, Austria). SSc-related manifestations were obtained from the Czech Registry of SSc patients. Skin changes were assessed using the modified Rodnan skin score and EUSTAR SSc activity score was determined. Data are presented as median (IQR). Results: Plasma levels of Hsp90 were comparable between SSc patients and healthy controls (10.8 (9.2–15.5) vs. 10.1 (8.2–12.8) ng/ml, p = 0.250) and between patients with diffuse cutaneous (dc) SSc and limited cutaneous (lc)SSc (11.6 (9.3–15.8) vs. 10.4 (8.6–15.6) ng/ml, p = 0.710). Of particular interest, the levels of Hsp90 positively correlated with EUSTAR SSc activity score (r = 0.418, p = 0.007). Furthermore, Hsp90 plasma levels negatively correlated with forced vital capacity (FVC), forced expiratory volume in 1s (FEV1) and diffusing capacity for carbon monoxide (DLCO) (r = - 0.457, p = 0.004; r = - 0.346, p = 0.033; r = - 0.444, p = 0.005, respectively). In addition, only in patients with dcSSc, Hsp90 levels positively correlated with the modified Rodnan skin score (r = 0.742, p = 0.022). Using Bonferroni's correction (p < 0.01), relations between Hsp90 and EUSTAR SSc activity score, FVC and DLCO were approved. The presence of autoantibodies (ANA, anti-centromere, anti-Scl70), a pathological capillaroscopic pattern (early, active, late), and exhibition of the main individual clinical symptoms of SSc did not significantly affect plasma levels of Hsp90. Conclusions: We demonstrate that plasma levels of Hsp90 are comparable between SSc patients and healthy controls. However, increased plasma levels of HSP90 in SSc patients are associated with higher disease activity, deteriorated parameters of lung involvement, and, particularly in dcSSc patients, with skin involvement. These data further highlight the role of Hsp90 as a regulator of fibroblast activation and tissue fibrosis in SSc. Reference: Tomcik M, Zerr P, Pitkowski J, et al . Heat shock protein 90 (Hsp90) inhibition targets canonical TGF-β signalling to prevent fibrosis. Ann Rheum Dis 2014; 73 (6):1215–22.